The Impact of Price and Promotion on Purchase Decisions with Trust as an Intervening Variable - Rakhmawati, Haniie; Susbiyani, Arik; Sanosra, Abadi; Qomariah, Nurul; Sari, Mutiara Dwi (Ilomata International Journal of Social Science, 2025)
This study analyzes the factors influencing consumer purchasing decisions for A3 Fresh O2 bottled drinking water (AMDK) in Bondowoso Regency, with a particular focus on the strategic roles of price and promotion, as well as the mediating effect of consumer trust. The research is motivated by observed fluctuations in sales volume over recent years, indicating market instability. Using a quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS), data were collected through a purposive sampling method involving 190 respondents. The study instrument was designed to capture the relationships among price, promotion, trust, and purchasing decisions. The findings indicate that price and promotion significantly influence both trust and purchasing decisions. Furthermore, consumer trust effectively mediates these relationships, although direct influences remain more dominant than indirect ones. The study offers managerial implications including the need for enhanced digital promotion, transparent product information, competitive pricing, and loyalty programs. Future research is encouraged to include additional variables such as brand loyalty and brand image to gain deeper insights into consumer behavior